Simplified synthesis of oxidized phospholipids on alkyl-amide scaffold - Olga V. Oskolkova; Bernd Gesslbauer; Valery Bochkov (MethodsX)
Oxidized phospholipids (OxPLs), containing oxidized fatty acids (oxylipins), play a significant role in various diseases. However, studying the structure-activity relationships of OxPLs and their signaling mechanisms is challenging due to the complexity of the chemical synthesis of structurally distinct lipid species. In this study, we aimed to develop a method for attaching free oxylipins to a lysophospholipid to form OxPLs. We hypothesized that oxylipins could be conjugated to PLs via a known chemical reaction between activated esters of carboxylic acids and amino groups. The carboxyl groups of oxylipins were activated using N-hydroxysuccinimide and a coupling reagent, then conjugated to a lyso-phosphatidylcholine containing NH2-groupd at sn-2 position, forming amide bonds. All reactions were performed under mild conditions and demonstrated high yields. To prevent acyl migration, the sn-1 position of PLs was modified with an alkyl residue linked via an ether bond. Several oxylipin-containing PLs were successfully synthesized, isolated, and characterized. The anti-TLR4 and endothelial barrier-protective activities of these alkyl-amide OxPLs were found to be equivalent to diacyl-OxPLs. This method enables efficient synthesis of modified OxPLs for biological testing. The combination of ether and amide bonds enhances biological stability and simplifies effect analysis. • The method describes the preparation of a single precursor for multiple choline PLs, specifically 2-deoxy-2-amino-1-lyso-sn-3-glycerophosphocholine, followed by the attachment of oxylipins to it. • No protection-deprotection steps are needed for oxylipins for the synthesis of phosphatidylcholines. • Isolation of compounds is performed using fast liquid-liquid and solid-phase extractions.